2006
DOI: 10.1029/2005rs003260
|View full text |Cite
|
Sign up to set email alerts
|

Current distribution of a VLF electric dipole antenna in the plasmasphere

Abstract: [1] In a recent paper (Inan et al., 2003) a method of remediating enhanced energetic electron fluxes in the radiation belt was proposed in which injection of VLF whistler mode waves from spacecraft within the radiation belts would dramatically increase the pitch angle scattering of the relativistic electrons and cause these particles to be rapidly lost from the belts, thereby mitigating the flux enhancement. The VLF wave transmitting system discussed by Inan et al. (2003) involves electric dipole antennas. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Thus one might expect, based on our findings, that the tuning circuit used to maximize the power delivered to the antenna would be the same for each dipole element, albeit complicated. It is also clear from our warm plasma findings that for frequencies above f LHR , the complex impedance of the antenna is dominated by the sheath characteristics as opposed to the almost perfectly tuned antenna that the cold plasma model predicts [ Bell et al , 2006].…”
Section: Resultsmentioning
confidence: 93%
“…Thus one might expect, based on our findings, that the tuning circuit used to maximize the power delivered to the antenna would be the same for each dipole element, albeit complicated. It is also clear from our warm plasma findings that for frequencies above f LHR , the complex impedance of the antenna is dominated by the sheath characteristics as opposed to the almost perfectly tuned antenna that the cold plasma model predicts [ Bell et al , 2006].…”
Section: Resultsmentioning
confidence: 93%
“…Theories of VLF power radiation into a magnetized plasma currently lack consensus and verification, despite substantial analysis [ Wang and Bell , 1972; Bell et al , 2006; Song et al , 2007; Krafft and Zaboronkova , 2010], numerical simulation [ Tu et al , 2008; Chevalier et al , 2010], and experimental studies [ James , 2003; Paznukhov et al , 2010; Pribyl et al , 2010]. One notable theoretical expectation is that VLF waves are radiated most effectively at wavelengths comparable to the antenna length.…”
Section: Graphical Approachmentioning
confidence: 99%
“…This slow decay rate distinguishes the generation of the whistler waves by magnetic dipole and the RMF source antennas from the generation of whistler waves by an electric dipole antenna, which has been studied by many authors theoretically, experimentally, and numerically. [12][13][14][15][16][17][18] In Ref. 14 it is clearly demonstrated that in the case of linear small magnitude whistler waves driven by the electric dipole antenna the magnitude of the wave decays very fast along the ambient magnetic field even in the collisionless plasma due to the fact that the energy radiated is nearly evenly distributed inside the resonance cone.…”
Section: Comparison Of Emhd Model and Experimentsmentioning
confidence: 99%